A BIM-IPD Integrated Framework For Reducing Disputes In Construction Projects In Egypt - Othman, Ayman; Sayed, Alaa (International Journal of Sustainable Construction Engineering and Technology, 2025)
Disputes remain a persistent challenge in Egyptian construction projects, due to traditional procurement approaches that hinder effective communication, coordination, and collaboration. As Egypt continues investing in mega construction projects, these issues are exacerbated despite the adoption of various management strategies. This study explores how incorporating Integrated Project Delivery (IPD) and Building Information Modelling (BIM) can enhance collaboration, transparency, and project coordination to mitigate disputes. A mixed-methods research approach incorporating literature review, case studies, and survey of large contractors in Egypt was employed to assess dispute causes, their impacts, and the role of IPD and BIM in reducing disputes. Findings indicate that time extensions and work delays are the primary dispute triggers, leading to project delays and cost overruns. Although BIM awareness is high (85%), only 48% of respondents are familiar with IPD, yet 94% recognize BIM’s role in supporting IPD, and 95% emphasize the need for an integrated framework. Case studies demonstrated that IPD significantly improves project performance and reduces disputes compared to traditional procurement methods, though design-bid-build remains the dominant contract type. The study also identifies significant organizational and legal challenges in implementing IPD and BIM, with a strong correlation between the two, while technological and legal challenges show a weaker connection. In response, a novel framework was developed to integrate BIM and IPD, addressing dispute causes and implementation barriers. This framework provides a structured approach outlining essential activities, tools, techniques, involved personnel, required resources, and implementation strategies, presenting an original synthesis that received limited attention in construction literature.